2020
DOI: 10.1186/s12894-020-00760-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COL1A1 and COL6A1 expression on hypospadias and penile curvature severity

Abstract: Background Hypospadias, the most frequent congenital male external genitalia abnormality, is usually associated with curvature of the ventral penis, i.e. chordee. Abnormality of darto tissue has been suggested as the pathophysiology of chordees. Collagen is one of the most abundant fibrous proteins within the extracellular matrix. In this study, we determined the expression of collagen 1 (COL1A1) and COL6A1 in patients with hypospadias and associated them with the severity of penile curvature. Methods We incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Several studies have proved inelastic dartos tissue in hypospadias. The abnormal findings were found in smooth muscle fiber [ 20 ], collagen I and VI [ 4 ], total collagen, elastin, and reticulin [ 6 ]. Even though dartos tissue has abnormal development of some ECM structure, this study found that dartos tissue has well vascularization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have proved inelastic dartos tissue in hypospadias. The abnormal findings were found in smooth muscle fiber [ 20 ], collagen I and VI [ 4 ], total collagen, elastin, and reticulin [ 6 ]. Even though dartos tissue has abnormal development of some ECM structure, this study found that dartos tissue has well vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…There are contrasting studies of histopathological aspects of connective tissue in patients with hypospadias. The dartos fascia of hypospadias had abnormal tissue that gave it the thick and inelastic character [ 4 , 5 ]. Inelastic dartos fascia tissue in patients diagnosed with hypospadias is a pathological tissue [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are four main mechanisms of congenital curvatures development: cutaneous or subcutaneous chord, the disproportion of the corpus cavernosum, or congenitally short urethra [ 2 ]. The congenital type is genetic; aberrant expression of COL1A1 and COL6A1 affects tunica dartos abnormalities and the severity of curvature [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on severity the curvature can be insignificant (less than 20 degrees), mild (20–30 degrees), moderate (30–60 degrees), and severe (more than 60 degrees) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%